2021
DOI: 10.1038/s41598-021-94817-x
|View full text |Cite
|
Sign up to set email alerts
|

Performance assessment of a multi-epitope chimeric antigen for the serological diagnosis of acute Mayaro fever

Abstract: Mayaro virus (MAYV), which causes mayaro fever, is endemic to limited regions of South America that may expand due to the possible involvement of Aedes spp. mosquitoes in its transmission. Its effective control will require the accurate identification of infected individuals, which has been restricted to nucleic acid-based tests due to similarities with other emerging members of the Alphavirus genus of the Togaviridae family; both in structure and clinical symptoms. Serological tests have a more significant po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 60 publications
(55 reference statements)
0
7
0
Order By: Relevance
“…The IgG immunodominant epitopes were the same as the ones previously described in Asian, European, or North American epitope mapping studies 1 11 . Taken together, the immune epitopes found in this study may help the development of epitope-based serological diagnostic assays or effective vaccine candidates 12 .…”
Section: Introductionmentioning
confidence: 69%
“…The IgG immunodominant epitopes were the same as the ones previously described in Asian, European, or North American epitope mapping studies 1 11 . Taken together, the immune epitopes found in this study may help the development of epitope-based serological diagnostic assays or effective vaccine candidates 12 .…”
Section: Introductionmentioning
confidence: 69%
“…The performance of selected epitopes strongly supports the continued use of these epitopes with a chimeric multi-epitope protein [59] as a target in more sensitive and fast diagnostic tests and suggests that the antigen may be eligible to enter phase IIB studies [60].…”
Section: Discussionmentioning
confidence: 77%
“…Tetanus is diagnosed by the patient's history and clinical signs [63] since there are no universal disposable laboratory tests [64]. Thus, concerning the diagnosis, our ELISA-peptide results using the MAP4 epitope peptides revealed that all four epitopes appropriately discriminated between negative and positive samples (p < 0.0001).…”
Section: Discussionmentioning
confidence: 86%